Unveiling the interplay of medical professionalism, mental well-being and coping in medical students: a qualitative phenomenological study - Kamran Sattar; Muhamad Saiful Bahri Yusoff (BMC Medical Education)
Abstract Background Medical students face significant stress and challenges that impact their professional development by affecting their levels of medical professionalism (MP), coping ability, and mental well-being (MWB). Given the high-stakes environment of medical education, understanding the interplay between these factors is crucial. This study aims to explore undergraduate medical students’ lived experiences of MP, coping strategies (CSs), and MWB to inform the development of effective support systems. Methods A qualitative phenomenological study was conducted using Focus Group Discussions (FGDs) to capture the lived experiences of 40 medical students from first, third, and fifth years of study. Participants, selected through purposive sampling, represented diverse backgrounds (with 27 females, 18 fifth-year students, and 30 Malays). Seven FGDs, each with 5–10 participants, were conducted via Zoom©, yielding comprehensive qualitative data. An inductive coding approach was applied through iterative transcript analysis to ensure robust findings. Results Analysis revealed two themes related to MWB: ‘mental well-being issues,’ highlighting persistent mental health challenges, and ‘happiness,’ illustrating factors that sustain well-being. CSs were categorized into ‘positive coping,’ including seeking support, and ‘negative coping,’ such as denial. For MP, two themes emerged: ‘inter-medical professionalism,’ focusing on communication with others, and ‘intra-medical professionalism,’ emphasizing ethical self-conduct. Conclusion The interplay between CSs, MP, and MWB is complex and deeply intertwined. The findings highlight the importance of developing targeted interventions to support medical students in managing stress, maintaining professionalism, and enhancing their mental well-being throughout their training. Future research should further explore these themes to inform policy and curriculum development in medical education. Clinical trial number Not applicable.